Sejarah Islam Indonesia (Dari Periode Awal hingga Munculnya Kerajaan Islam) - Ahmad Asroni (Neolectura, 2022)
This article examines the history of the arrival of Islam into Indonesia. This research is library research using documentation method. The results of this study are: First, no one knows for sure when Islam began to appear in Indonesia. Several theorists and historians have different opinions and analyzes. However, there are at least four major theories regarding the entry of Islam into Indonesia, namely: Arabic theory, Gujarat theory (India), Bengali theory (Fatimi), and Persian theory. Second, the spread and process of Islamization in Indonesia itself was carried out peacefully. Indonesian people can accept the existence of Islam well. There are six channels of Islamization in Indonesia, namely: trade, marriage, Sufism, education, arts and culture, and politics. Third, the existence of Islamic kingdoms also had a big role in the spread and development of Islam in Indonesia. These Islamic kingdoms stretched from Sumatra to the Moluccas. Some of them are the Perlak Sultanate, Samudera Pasai Sultanate, Malacca Sultanate, Aceh Sultanate, Demak Sultanate, Pajang Sultanate, Mataram Sultanate, Cirebon Sultanate, Banten Sultanate, Sultanate of Ternate, Sultanate of Tidore, Sultanate of Gowa, Sultanate of Tallo, Sultanate of Pasir, Sultanate of Banjar, Kotawaringin Sultanate, Pagatan Sultanate, Sambas Sultanate, Kutai Kertanegara Sultanate, Berau Sultanate, Sambaliung Sultanate, Gunung Tabur Sultanate, Pontianak Sultanate, Tidung Sultanate, and Bulungan Sultanate.